Audio visual cabinet with storage function / Mohd Asri Ismail - Ismail, Mohd Asri (2003)
This paper discussed about the manufacturing of Audio Visual storage Cabinet. The Audio Visual is one of the cabinets in houses. The function of this cabinet is to load the media devices such as television, Hi-Fi, VCD Player, Subwoofer, CD rack, amplifier and other devices. The motive made of this Audio Visual cabinet is to make the room neat and orderly and as the result the room will be more comfort and harmony. (David J.H.1994) was said that Cabinet and counter dimension are very important. With the little imagination, the alternatives can be made to facilitate even greater and more organized home storage cabinet. This product was covered the old and other design with new function which is not include in other audio visual cabinet such as a speaker part, subwoofer part CD storage function and using the MDF. Medium Density fibreboard (MDF), a wood based composite material is used as raw material in this cabinet making. It is typically made as a board type product, though it's use in mouldings and increasing use, as a structural product will see beam type products proliferate. It is supplement to other wisp in furniture product cabinet making, joinery, craftwork and flooring. Its advantage includes suitable, good working properties, good weathering properties and the ability to be made from a wide variety of fibrous products. Others materials such as glass, plywood are also used. Types of fasteners used were screw and Allen key as jointing method.